Adeno-associated virus vector-based gene therapies for pediatric diseases - Kazuhiro Muramatsu; Shin-ichi Muramatsu (Elsevier, 2023)
Gene therapy using adeno-associated virus (AAV) is a rapidly developing technology with widespread treatment potential. AAV2 vectors injected directly into the brain by stereotaxic brain surgery have shown good results in treating aromatic l-amino acid decarboxylase deficiency. Moreover, gene therapy using the AAV9 vector, which crosses the blood-brain barrier, has been performed in more than 2000 patients worldwide as a disease-modifying therapy for spinal muscular atrophy. AAV vectors have been applied to the development of gene therapies for various pediatric diseases. Gene therapy trials for hemophilia and ornithine transcarbamylase deficiency are underway. Clinical trials are planned for glucose transporter I deficiency, Niemann-Pick disease type C, and spinocerebellar ataxia type 1. The genome of AAV vectors is located in the episome and is rarely integrated into chromosomes, making the vectors safe. However, serious adverse events such as hepatic failure and thrombotic microangiopathy have been reported, and ongoing studies are focusing on developing more efficient vectors to reduce required dosages.